Nurses' Experiences Of Factors Affecting Job Motivation: A Qualitative Study (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Motivation is a complex process that includes individual, organizational, and social factors, and the performance of organization employees depends on their ability and motivation. Knowing and analyzing motivational factors is very significant. This study was conducted with the aim of explaining nurses' experiences of the factors affecting job motivation.Methodology: An in-depth and semi-structured interview was conducted with nurses from affiliated hospitals of Birjand University of Medical Sciences for this study, which is a type of content analysis. With their consent, the participants' statements were recorded and then handwritten word by word. Participants' statements were recorded and then handwritten word by word with their consent. Eight participants participated in the study, depending on data saturation, and saturation occurred when no new information was obtained during data analysis and coding. Data analysis was done simultaneously with data collection using the content and Greenheim methods.Findings: From the content analysis regarding nurses' experiences of the factors affecting career motivation, five categories, including individual self-motivational factors, professional motivational factors, management motivational factors, financial motivational factors, and educational motivational factors, and ten subcategories, including motivational personality dimensions, moral motivators, professional conditions, professional dignity, manager's personality dimensions, management style, receiving an appropriate salary, reward, trainer's personality dimensions, and clinical environment were extracted.Conclusion: The results of this study indicate that nursing managers can take steps towards maintaining and improving nurse job motivation by paying greater attention to internal motivation factors. Consequently, they will be able to provide nursing care of a higher quality and find effective and constructive solutions for the development of healthcare organizations that play a vital role in the health of society.